The Use of a Two-Phase Online Delphi Panel Methodology to Inform the Concurrent Development of a School-Based Ovulatory Menstrual Health Literacy Intervention and Questionnaire - Roux, Felicity; Burns, Sharyn; Chih, HuiJun; Hendriks, Jacqueline (Frontiers in Global Women's Health, 2022)
Introduction There are a high prevalence of ovulatory-menstrual (OM) dysfunction and low levels of menstrual health literacy in adolescents, yet few evidence-based OM health education resources for schools. Method This two-phase study used an online Delphi methodology to build consensus across thirty-five purposively selected professionals from the diverse professions of health and education. The panellists were tasked to inform the development of a school-based OM health literacy resources. Results In Round One, 86% of panellists determined the scope of these resources using guided and open-ended questions. The study then split into two phases which ran concurrently. In the first phase informing the intervention's development, 57% of panellists participated in Round Two, and 29% reviewed selected lessons. In the second phase informing the questionnaire's development, 51% of panellists participated in Round Two, and 69% in Round Three. The overall consensus reached for the intervention phase and questionnaire phase were 82% and 84%, respectively. The Panel's recommendations included a strengths-based position to counter menstrual stigma, teaching accurate self-report of cycle biomarkers, addressing multiple menstrual dysfunctions and adopting a whole-school approach. Conclusion Although time-consuming and requiring a sustained interest, this two-phase Delphi methodology offered anonymity to panellists from distinct professions which facilitated their independent contribution to developing OM health literacy school resources.